The Albert Memmi reader - Memmi, Albert (France overseas., 2020)
"This anthology presents Albert Memmi's insights on the legacies of the colonial era, critical theories of race, and his own story as a French writer of Tunisian and Jewish descent, allowing readers to appreciate the full arc of one of the great thinkers of the twentieth century"--